Exploration of Bis(nickelation) of 1,1′-Bis(o-carborane) - Dipendu Mandal; Georgina M. Rosair (Crystals, 2020)
The metalation of [Tl]2[1-(1′-3′,1′,2′-closo-TlC2B9H10)-3,1,2-closo-TlC2B9H10], with the smaller {Ni(dmpe)} fragment sourced from [Ni(dmpe)Cl2], is explored. The bis(metalated) products are obtained as a diastereoisomeric mixture. These isomers were separated, fully characterised spectroscopically and crystallographically and identified as rac-[1-(1′-3′-(dmpe)-3′,1′,2′-closo-NiC2B9H10)-3-(dmpe)-3,1,2-closo-NiC2B9H10] (1) and meso-[1-(1′-3′-(dmpe)-3′,1′,2′-closo-NiC2B9H10)-3-(dmpe)-3,1,2-closo-NiC2B9H10] (2). Previously, these 3,1,2-NiC2B9-3′,1′,2′-NiC2B9 architectures (where both cages are not isomerised), were inaccessible, and thus new structures can be achieved during bis(nickelation) with {Ni(dmpe)}. Further, the metalation of the tetra-thallium salt with the bulky {Ni(dppe)} fragment sourced from [Ni(dppe)Cl2] was also studied. These bis(nickelated) products were also fully characterised and are afforded as the stereospecific species rac-[1-(1′-3′-(dppe)-3′,1′,2′-closo-NiC2B9H10)-3-(dppe)-3,1,2-closo-NiC2B9H10] (3) and [1-(2′-4′-(dppe)-4′,1′,2′-closo-NiC2B9H10)-3-(dppe)-3,1,2-closo-NiC2B9H10] (4α). In the latter metalation, compound 3 shows intramolecular dihydrogen bonding, contributing to the stereospecificity, whereas isomerisation from 3,1,2 to 4,1,2- in the 4α is related to steric relief.